Estimation of Frequencies for National Shortwave Network with Automatic Link Establishment Equipment - Machado Fernández, José Raúl; Lorenzo Rodríguez, Yoanne; Gutiérrez Vázquez, Yaser; León Rosich, David (Ingeniería, 2017)
Transmission over High Frequency (HF) is a very important alternative to the wired communication. Though it offers narrow bandwidths, long distances are reachable with it so the mechanism is commonly used as a backup connection for exceptional situations. The Automatic Link Establishment (ALE) technique is a new solution that tries to release the HF operators from the arduous task of finding the most favored communication frequency. Recently, a wireless HF network based on ALE has been proposed for interconnecting the western, central and eastern Cuban regions with the Havana capital city. While the technology ensures high stability in communications, it requires the a priori configuration of a frequency set for each established link. Authors of the present paper use the VOACAP software to predict the ten optimal communication frequencies for the period 2014 - 2018, in an analysis that allows the adaptation of the chosen set in an annual or monthly basis, depending on user needs. The results are also compared with estimates for the years 2012 and 2013, completing thus the progression analysis of the general behavior and its dependence on ionospheric conditions.